Achieving Aichi Biodiversity Target 11 to improve the performance of protected areas and conserve freshwater biodiversity. (June 2016) - Juffe‐Bignoli, Diego; Harrison, Ian; Butchart, Stuart HM; Flitcroft, Rebecca; Hermoso, Virgilio; Jonas, Harry; Lukasiewicz, Anna; Thieme, Michele; Turak, Eren; Bingham, Heather; Dalton, James; Darwall, William; et al.
Abstract: The Strategic Plan for Biodiversity (2011–2020), adopted at the 10th meeting of the Conference of the Parties to the Convention on Biological Diversity, sets 20 Aichi Biodiversity Targets to be met by 2020 to address biodiversity loss and ensure its sustainable and equitable use. Aichi Biodiversity Target 11 describes what an improved conservation network would look like for marine, terrestrial and inland water areas, including freshwater ecosystems. To date, there is no comprehensive assessment of what needs to be achieved to meet Target 11 for freshwater biodiversity. Reports on implementation often fail to consider explicitly freshwater ecosystem processes and habitats, the pressures upon them, and therefore the full range of requirements and actions needed to sustain them. Here the current progress and key gaps for meeting Aichi Target 11 are assessed by exploring the implications of each of its clauses for freshwater biodiversity. Concerted action on Aichi Biodiversity Target 11 for freshwater biodiversity by 2020 is required in a number of areas: a robust baseline is needed for each of the clauses described here at national and global scales; designation of new protected areas or expansion of existing protected areas to cover known areas of importance for biodiversity and ecosystem services, and a representative sample of biodiversity; use of Other Effective Area‐Based Conservation Measures (OECMs) in places where designating a protected area is not appropriate; and promoting and implementing better management strategies for fresh water in protected areas that consider its inherent connectivity, contextual vulnerability, and required human and technical capacity. Considering the specific requirements of freshwater systems through Aichi Biodiversity Target 11 has long‐term value to the Sustainable Development Goals discussions and global conservation policy agenda into the coming decades. Copyright © 2016 John Wiley & Sons, Ltd.